计算 (1)(-2a)^3-(-a)×(-2a)^2 (2)(-2×10^12)÷(-2×10^3)^3÷(0.5×10^2)^2

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/14 22:45:34
计算 (1)(-2a)^3-(-a)×(-2a)^2 (2)(-2×10^12)÷(-2×10^3)^3÷(0.5×10^2)^2
x){nu0|H%qƺ 6yx:BtC8Cv1X;X@,dkTOW lC-յHTS6462(\Je cv U ~RC}C<;P l

计算 (1)(-2a)^3-(-a)×(-2a)^2 (2)(-2×10^12)÷(-2×10^3)^3÷(0.5×10^2)^2
计算 (1)(-2a)^3-(-a)×(-2a)^2 (2)(-2×10^12)÷(-2×10^3)^3÷(0.5×10^2)^2

计算 (1)(-2a)^3-(-a)×(-2a)^2 (2)(-2×10^12)÷(-2×10^3)^3÷(0.5×10^2)^2
(1)(-2a)^3-(-a)×(-2a)^2
=-8a³+4a³
=-4a³
(2)(-2×10^12)÷(-2×10^3)^3÷(0.5×10^2)^2
=-2×10^12÷(-8×(1/4)×10^13)
=1/10